Acetylation of Orange Waste For Possible Industrial Use - Ayedun, H.; Oyede, R.T.; Osinfade, B.G.; Umar, B.F.; Oderinde, A.A.; Oguntade, B.K. (Asian Journal of Chemistry, 2011)
Orange mesocarp were acetylated using acetic acid and acetic anhydride with 0.1 M tetra oxosulfate(vi) acid as catalyst. The acetyation of pure cellulose was carried out in comparison with orange mesocarp. The percentage acetyl content of the products were determined using titration method. The percentage acetyl is higher in cotton cellulose than in orange mesocarp. The infrared spectral of the product was recorded using Perkin-Elmer model 710 B spectrophotometer with KBr disc. The C=O stretch appear at 1757-1630 cm-1 for cellulose and 1666-1563 cm-1 for orange mesocarp, while the -OH stretch appear around 3600-3100 cm-1 for cotton and 3500-3381 cm-1 for orange mesocarp. It was concluded that with further work on this research on industrial scale, orange waste could be a good source of raw materials for textile industries.